Study of the molecular clump associated with the high-energy source HESS J1858+020 - Paron, Sergio Ariel (2011)
Aims. HESS J1858+020 is a weak γ-ray source lying near the southern border of the SNR G35.6-0.4. A molecular cloud, composed of two clumps, shows signs of interaction with both the SNR and a nearby extended HII region. In particular, the southernmost clump coincides with the center of the H.E.S.S. source. We study this clump in detail to help us identify the nature of the very-high energy emission. Methods. We observed the aforementioned molecular clump using the Atacama Submillimeter Telescope Experiment (ASTE) in the 12CO J = 3−2, 13CO J = 3−2, HCO+J = 4−3, and CS J = 7−6 lines with an angular resolution of 22′′. To complement these observations, we analyzed IR and submillimeter continuum archival data. Results. From the 12CO and 13CO J = 3−2 lines and the 1.1 mm continuum emission, we derive a density of between 103 and 4 cm-3 for the clump. We discover a young stellar object (YSO), probably a high mass protostar, embedded in the molecular clump. However, we do not find any evidence of molecular outflows from this YSO that would represent a thermal jet capable of generating the observed γ-rays. We conclude that the most probable origin of the TeV γ-ray emission is a hadronic interaction between the molecular gas and the cosmic rays accelerated by the shock front of the SNR G35.6-0.4.